평택시 슈퍼오닝 유통회사 타당성 검토 - 국승용 (한국농촌경제연구원, 2009)
‘Super O’ning’ is the brand name of agricultural products which are produced in Pyeongtaek City. Pyeongtaek City has a plan to establish marketing company for Super O’ning products. The purpose of this study is to make marketing plan for Super O’ning marketing company and to analyze feasibility of its establishment. To make marketing plan, we considered two different marketing strategies, such as outbound marketing and local food marketing. Outbound marketing means sell their local specialties in large market, or export them to global market. And local food marketing menas sell many kinds of their agricultural products to their citizens. Rice and pear have been traditionally representative agricultural products of Pyeongtaek City. So existing farmers' marketing organization are concentrating their marketing forces to sell them. If Super O’ning marketing company make plan to sell rice or pear, it is unvoidable to compete with each other. This is a sensible solution, that Super O’ning marketing company should focus on local food marketing. School meal supply, membership vegetable basket marketing, and supply of local products to stores and restaurant will be main business of Super O’ning marketing company. Super O’ning marketing company will contribute in developing local food movement or community support agriculture, which is relatively popular in western countries. Citizens in Pyeongtaek City eat 62,532 tons of vegetables a year. Most of vegetables produced in Pyeongtaek City are transported to wholesale markets in Seoul, and they are re-transported to Pyeongtaek City. If Super O’ning marketing company can deal 20% of vegetables in their region, Pyeongtaek citizens can reduce 1.7 billion won distribution cost annually. Establishment of Super O’ning marketing company costs 1.9 billion won for next five years, however. In conclusion, it is reasonable that Pyeongtaek City organize Super O’ning marketing company, and make it concentrate on local food market. Researchers: Gouk Seung-yong , Kim Dong-hoon E-mail: gouksy@krei.re.kr